2011
DOI: 10.1111/j.1365-2982.2011.01796.x
|View full text |Cite
|
Sign up to set email alerts
|

The anxiolytic effect of Bifidobacterium longum NCC3001 involves vagal pathways for gut-brain communication

Abstract: In this colitis model, anxiety-like behavior is vagally mediated. The anxiolytic effect of B. longum requires vagal integrity but does not involve gut immuno-modulation or production of BDNF by neuronal cells. As B. longum decreases excitability of enteric neurons, it may signal to the central nervous system by activating vagal pathways at the level of the enteric nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
579
3
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 835 publications
(644 citation statements)
references
References 27 publications
23
579
3
12
Order By: Relevance
“…Treatment with Bifidobacterium longum abolished such behavior. However, the anxiolytic effect of Bifidobacterium longum was absent in vagotomized mice, suggesting that the effect was transmitted to the central nervous system by activating vagal pathways at the level of the enteric nervous system (9). It is thus intriguing to note that in our study the amount of the same species was found to be decreased in early life in children later developing ADHD or AS.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Treatment with Bifidobacterium longum abolished such behavior. However, the anxiolytic effect of Bifidobacterium longum was absent in vagotomized mice, suggesting that the effect was transmitted to the central nervous system by activating vagal pathways at the level of the enteric nervous system (9). It is thus intriguing to note that in our study the amount of the same species was found to be decreased in early life in children later developing ADHD or AS.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, the search for etiologies has been expanded both within the central nervous system and beyond. Experimental data are accumulating to suggest that the presence of gut microbiota as such, as compared with the absence of it, and especially its certain beneficial bacteria, probiotics, make for altered function within the nervous system (8)(9)(10)(11)(12). As a recent empirical study indicates (13) probiotics may provide a tool to manipulate brain activity even in humans.…”
mentioning
confidence: 99%
“…88 Furthermore, intraduodenal administration of a non-pathogenic bacterium, Bifidobacterium longum, is anxiolytic but also requires an intact vagus. 89 Another anxiolytic probiotic, Lactobacillus rhamnosus, results in region specific change in the expression of GABA receptor subunits. GABA type B subunit 1 isoform b (GABAB1b) mRNA was decreased in the amygdala and hippocampus, while increased in cortical areas.…”
Section: Effect Of Bacterial Metabolites On the Central Nervous Systemmentioning
confidence: 99%
“…60 Other events that lead to a change in the composition of gut microbiota such as infection or use of probiotics can also change the level of anxiety. 89,[103][104][105] Further, it is shown that the behavioral phenotype of anxietyprone strains of mice is also dependent on their existing microbiota. For example, BALB/c mice exhibit a highly anxious phenotype that does not show much exploratory locomotion in a new environment, while NIH Swiss mice show less anxiety and more exploratory motions in the same environment.…”
Section: Stress Response and Anxietymentioning
confidence: 99%
“…In addition to the direct effects of nutrients and dietary factors on neurodevelopmental endpoints, indirect effects may arise from links between the early diet on gut growth, enteric nervous system, signaling molecules like serotonin (5-HT), and/ or gut microbiota. Studies in mice show that changes in the gut microbiota after birth, in parallel with the first enteral feeding, lead to an anxiety-depression-like behavior (13) and other behavioral changes (14). Whether such effects are mediated by changes in gut physiology and microbiology, resulting in metabolic, endocrine, or neuronal effects on the brain and central nervous system (CNS), are unknown.…”
mentioning
confidence: 99%